Deconstructing Development: Postmodern Analysis of Socializing National Cinema in Nepal (Research Nepal Journal of Development Studies, 2025)
Deconstructing the development of national cinema begins with blending diverse socio-cultural aspects in cinema. This study discusses socializing Nepali national cinema from postmodern viewpoint. The study is grounded in phenomenological understanding of film as a situated experience and the critical discourse that shapes cinematic principles. In doing so, the study used library based research method and reviewed 36 papers related to film ethnography, film studies curricula, and legal side of film industry as well as representation of gender and subaltern voices. During the analysis, the theoretical insights are brought from postmodern and socialization theories. The study found that back in the early days, Nepali Cinema built strong national identity through centralized state control mechanism. After 1990s, Nepali Cinema becomes diverse with parallel cinema and focused on socio-cultural aspects and ethnographic themes. After the Maoist insurgency, it started showing indigenous cultures and groups that were marginalized. National Film Development Board (FDB) also seems responsible with function of Censorship. It is becoming major state tool for maintaining social harmony.  The study concludes that Nepali cinema has been shifting from centralized nationalism into more scattered ethnic pluralism that comes up in postmodern ways. National cinema breaks down ideas about development and gets people thinking critically about society. For the betterment, FDB must introduce a grading system for content with ethical guidelines. They could fund stories from marginalized groups and attract educated skillful newcomers in film industry. Provincial government and local government must provide technical and financial support to the film industry. They can formed community forums to establish interactive theatre setups and to perform their unique socio-cultural aspects. The film industry must socializing diverse ethnographic stories from a postmodern viewpoint.